Direct and indirect effects of attachment orientation on relationship quality and constraint commitment in married couples. Issue 2 (3rd April 2019) - Givertz, Michelle; Woszidlo, Alesia; Segrin, Chris; Jia, Qiaozhen
ABSTRACT: This study examined the associations between attachment orientation, relationship quality, and constraint commitment. It tested the prediction that insecure attachment would be negatively associated with constraint commitment, that relationship quality would be positively associated with constraint commitment, and that there would be an indirect effect of attachment insecurity on lower constraint commitment through lower relationship quality. Parallel research questions were advanced to examine if there were corresponding partner effects. Predictions were tested on 628 married couples. Tests of actor-partner interdependence revealed that attachment insecurity was associated with lower constraint commitment for both husbands and wives, and that husbands' attachment insecurity was associated with wives' lower constraint commitment. These same tests revealed a positive association between relationship quality and constraint commitment for husbands and wives. Tests of actor-partner interdependence mediation models revealed that attachment insecurity was indirectly associated with lower constraint commitment through lower relationship quality for both husbands and wives, and that husbands' attachment insecurity was associated with wives' lower constraint commitment through wives' lower relationship quality. This study extends previous research on attachment and commitment by demonstrating that an insecure attachment orientation is associated with perceptions of lower constraint commitment through lower relationship quality, suggesting that relationship quality plays an important role in explaining the association between attachment orientation and constraint commitment.